Geochemistry of the tailings - pond water interface in the flooded tailings pond at Stekenjokk, northern Sweden - Öhlander, Björn; Holmström, Henning (Luleå tekniska universitet, Geovetenskap och miljöteknik, 2000)
Godkänd; 2000; 20080227 (ysko)